Glutamine synthetase expression in the brain during experimental acute liver failure (immunohistochemical study) - Shulyatnikova, T.; Tumanskiy, V. (Journal of Education, Health and Sport, 2021)
The aim of the study was to determine the immunohistochemical level of glutamine synthetase (GS) expression in different brain regions in the conditions of experimental acute liver failure in rats. Materials and methods. The study was conducted in Wistar rats: 5 sham (control) animals and 10 rats with acetaminophen induced liver failure model (AILF). The immunohistochemical study of GS expression in the sensorimotor cortex, white matter, hippocampus, thalamus, caudate nucleus/putamen was carried out in the period of 12-24 h after acetaminophen treatment. Results. Beginning from the 6th hour after acetaminophen treatment all AILF-animals showed the progressive increase in clinical signs of acute brain disfunction finished in 6 rats by comatose state up to 24 h - they constituted subgroup AILF-B, “non-survived”. 4 animals survived until the 24 h - subgroup AILF-A, “survived”. In the AILF-B group, starting from 16 to 24 hours after treatment, a significant (relative to control) regionally-specific dynamic increase in the level of GS expression was observed in the brain: in the cortex – by 307.33 %, in the thalamus – by 249.47%, in the hippocampus – by 245.53%, in the subcortical white matter – by 126.08%, from 12th hour – in the caudate nucleus/putamen, by 191.66 %; with the most substantive elevation of GS expression in the cortex: by 4.07 times. Conclusion. Starting from the 16th hours after the acetaminophen treatment (from the 12th h in the caudate nucleus/putamen region) and up to 24 h, it is observed reliable compared to control dynamic increase in GS protein expression in the cortex, white matter, hippocampus, thalamus, caudate nucleus/putamen of the rat brain with the most significant elevation in the cortex among other regions. The heterogeneity in the degree of GS expression rising in different brain regions potentially may indicate regions more permeable for ammonia and/or other systemic toxic factors as well as heterogeneous sensitivity of brain regions to deleterious agents in conditions of AILF. Subsequently, revealed diversity in the GS expression reflects the specificity of reactive response of local astroglia in the condition of AILF-encephalopathy during specific time-period. The dynamic increase in the GS expression associated with impairment of animal state, indicates involvement of increased GS levels in the mechanisms of experimental acute hepatic encephalopathy.